2003
DOI: 10.1029/2002ja009419
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and catastrophe of coronal flux ropes in axisymmetrical magnetic field

Abstract: [1] Using a 2.5-dimensional, time-dependent ideal magnetohydrodynamic model in spherical coordinates, we present a numerical study of the property of magnetostatic equilibria associated with a coronal magnetic flux rope embedded in an axisymmetrical background magnetic field. The background field is potential (either closed or partly opened), a magnetic flux rope emerges out of the solar surface, and the resultant system is allowed to relax to equilibrium through numerical simulation. It is shown that the flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 29 publications
5
66
1
1
Order By: Relevance
“…In terms of a 2.5-D flux rope model in spherical coordinates, Hu et al (2003) concluded that W c is slightly larger than W open , and the gravity associated with the prominence supported by the flux rope raises W c by an amount that is approximately equal to the magnitude of the excess gravitational energy associated with the prominence. Such a conclusion was further quantified by : W c exceeds W open by 8%.…”
Section: Catastrophic Energy Threshold Of the Flux Rope Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of a 2.5-D flux rope model in spherical coordinates, Hu et al (2003) concluded that W c is slightly larger than W open , and the gravity associated with the prominence supported by the flux rope raises W c by an amount that is approximately equal to the magnitude of the excess gravitational energy associated with the prominence. Such a conclusion was further quantified by : W c exceeds W open by 8%.…”
Section: Catastrophic Energy Threshold Of the Flux Rope Systemmentioning
confidence: 99%
“…In an extension of the flux rope model to spherical geometry, Hu et al (2003) found that a flux rope embedded in a bipolar background field also exhibits a catastrophic behavior with respect to Φ p or Φ t , which does not depend on whether the background field is partly-open or closed. The rope sticks to the solar surface in equilibrium below the catastrophic point, and escapes to infinity above.…”
Section: Catastrophe Associated With the Rope Property Changementioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [93] managed to eliminate numerical reconnections across the CME current sheet and achieved numerical simulation of the flux rope eruption within the framework of ideal MHD. This is done by taking advantage of the fact that the magnetic flux function being a known constant along the current sheet [86]. This allows them to make a first-time quantitive comparison of energy releases for cases with and without magnetic reconnections.…”
Section: Energy Release Mechanisms Of Cmes: Mhd Studies With a Flux-rmentioning
confidence: 99%
“…In the former models, the pre-exisiting flux rope carries enough free energy driving the eruption. Both analytical rope models [24,85] and numerical rope models [29,86] have been developed under 2-D configuration. In these models, the rope system first evolves slowly with the boundary or the background conditions till a certain threshold is reached.…”
Section: Energy Release Mechanisms Of Cmes: Mhd Studies With a Flux-rmentioning
confidence: 99%